E-GOVERNANCE IN INDIA: A STEP TOWARDS SUSTAINABLE ADMINISTRATION (International Journal of Food and Nutritional Sciences, 2022)
The Indian government’s National E-governance plan aims, among the other things, to “Make all government services accessible to the common man in his locality through common service delivery outlets.” It was clear at the conference that the plan has achieved some success through a number of pilot projects. However, it was also evident that government alone cannot ensure “efficiency, transparency and reliability of such services at affordable costs.” The private sector should be actively participated in e-governance and it should play active role in spreading e- governance services across India. Thus, as the following report details, the conference recommended greater attention to public-private partnerships, policy reform and infrastructural changes as ways to deliver more efficient and effective e-governance across India.